Effective Evaluation of Open Defecation Free Program in Rural Municipality of Nepal (Sotang, Yearly Peer Reviewed Journal, 2020)
Open defecation practice is very common in Nepal. It causes a serious threat to the health of Nepalese people. Thus, Government of Nepal is committed to making Nepal open defecation free (ODF) by 2017 to promote health of people. This paper explore the current situation of open defecation practices in context to Nepal along with the effective evaluation of open defecation free program in regards to health promotion. It is based on review of the related literature to open defecation free and water supply, sanitation and hygiene in Nepal and effective evaluation of ODF program in rural municipality of Nepal. This study emerged mainly three themes for effective evaluation of open defecation free program that are evaluation stages of ODF program, evaluation criteria of ODF program, and evaluation methods and tools of ODF program along with various other sub themes to carry out ODF program evaluation in a effective manner. ODF is one of the effective community participation programs of Nepal. Thus, a lot of focus should be given on behavior and mind-set changes in community people in order to ensure sustainable of sanitation for all.